Geotechnical Challenges of Tehran Metro Line 7 (South Northern Route) - Farzad Sadjadi; Ahad Bagherzadeh Khalkhali (Salehan Institute of Higher Education, 2018)
Tunneling in urban areas, has raised the level of difficulty and challenge in respecting the constraints deriving from human presence and, therefore, the necessity for the study of geological and geotechnical properties and parameter, classification of the soils according to their engineering behavior, choosing the right TBM, determine groundwater level and determining possible geological hazards. In this paper some geological and geotechnical study took place along the tunnel route. This investigation is done by the result of 73 machinery borehole and 32 manual borehole that took place in the process of studying the tunnel route and continued by the result of field tests and laboratory tests and according to the result, the geological zone classified in 6 zone in tunnel route; due to the result of Cerchar abrasivity test and since Alluvial soil is the main soil in most of the tunneling route, the excavation soil classified as highly abrasive. In some part of tunneling there is a risk of clogging due to the high amount of clay. Based on the results of Lofran tests the permeability of most of the classified soils in route of the tunnel was obtained less that 10E-7 m/s.